English English - Wiraswari, Luh Muni; Agustin, Herlina; Al-Faqih, M. Zen (representamen, 2026)
The media is a source of information about the situation in West Papua for the public. Nevertheless, representations of West Papua in the media are fragmented, leading to a distorted public understanding of the region. This distortion, particularly among people outside West Papua, is caused by the Indonesian government’s dominance in the media. The Indonesian government’s dominance as authority creates unequal representation between the government’s narrative and the voices of Papuan, especially in the national media. This study aims to analyze the construction of discourse about West Papua in the media at three different levels of reach: local media, national media, and international media by literature review. This study found three different discourse patterns. The local media tended to prioritize a discourse of resistance that presented critical voices and highlighted Papuan identity in media texts. Meanwhile the national media was dominated by the discourse of national stability and sovereignty, which tended to be in line with the ideology of the Indonesian government. Last, the international media is more critical in highlighting human rights discourse. However, the media’s reach does not always determine the discourse in the media. Discourse on Papua in the media is also influenced by the media’s position in the social system and the ideology that surrounds it. However, over the past ten years, most research has focused solely on textual aspects and has not addressed the influence of ideology in media discourse. These findings indicate that there has been no significant progress in research on the relationship between ideology and media discourse regarding Papua. Therefore, new research is needed that integrates ideology with media, especially national online media, across various dimensions. This aims to reveal the power dynamics within media discourse.